Triple arched entrances with ox-eye window - Ghosh, Ayan (Jio Institute, 2023)
Design for the BMC was to be selected via a competition open to architects from London. First prize was won by RF Chisholm who proposed a Hindu-Saracenic style. However, the project got delayed by a few years as new sites were considered. During the delay, Chisholm's design fell out of favour with authorities and call was made for fresh proposals.